2018
DOI: 10.1111/mve.12337
|View full text |Cite
|
Sign up to set email alerts
|

First record and spreading of the invasive mosquito Aedes japonicus japonicus (Theobald, 1901) in Croatia

Abstract: Aedes (Hulecoeteomyia) japonicus japonicus (Theobald, 1901) has recently established across North America and Central Europe. A 3-year survey was conducted in northwestern Croatian regions from 2013 to 2015 using mosquito ovitraps at possible points of entry and house yards, occasionally complemented by larval collections from cemetery vases. In the first year, the survey investigated the county bordering Slovenia, where the first detection of Ae. j. japonicus had taken place on 28 August 2013. During the next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…j . japonicus already in the framework of a previous study [ 28 ], whereas locations found colonised in the present study and included in the population genetic analyses are marked by yellow dots. Numbers in the dots refer to the compilation of sampled locations in S1 Table , numbers of encirclements to the Croatian study areas (I = Slavonian Mountains, II = Gorski Kotar, III = Central Velebit).…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…j . japonicus already in the framework of a previous study [ 28 ], whereas locations found colonised in the present study and included in the population genetic analyses are marked by yellow dots. Numbers in the dots refer to the compilation of sampled locations in S1 Table , numbers of encirclements to the Croatian study areas (I = Slavonian Mountains, II = Gorski Kotar, III = Central Velebit).…”
Section: Methodsmentioning
confidence: 84%
“…j . japonicus in Croatia was made in 2013 when eggs were found during a survey for invasive mosquitoes in Krapinsko-Zagorska county, bordering Slovenia [ 28 ] where the species was widely distributed in 2015 [ 30 ]. The survey in Croatia included ovitrapping at possible points of entry and in house yards, occasionally complemented by larval collections from cemetery vases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…j. japonicus was the third non-native mosquito species recorded, 23 and since its first detection in the early 2000s, the species has been observed to expand its range and new records are reported continuously. [24][25][26][27][28][29][30][31][32] A niche unfilling within the new ranges in Europe and North America is very likely for Ae. j. japonicus due to the short time since its first detection on both continents.…”
Section: Introductionmentioning
confidence: 99%
“…japonicus was rst detected in Switzerland [2], in the north-west part of the country from where it spread and became widely established with locally high abundances. Recently, the species has established in other European countries [2] such as Austria, Croatia, Germany, Hungary, Italy, Liechtenstein, The Netherlands, Slovenia and Spain [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%